Erectile dysfunction - Nik Mohamed, Mohamad Haniki; Elnaem, Mohamed Hassan Abdelaziz; Draman, Samsul; ., Aziz-ur-Rahman (Malaysian Academy of Pharmacy, 2018)
The aim of this course is to share existing evidence on the diagnosis and management of patients suffering from erectile dysfunction (ED). ED is one of the main growing complaints among males. This course is planned for healthcare providers as a self-study course and assessment materials to ensure that by the upon completion of this course, you will have the understanding and details about the epidemiology, aetiology and pathophysiology, diagnosis, management and treatment options for the ED patients and last but not the least about the pharmacist’s role in the management and counselling of ED patients. We hope that you will find this course useful not only to collect CPD points (A8: 3 CPD Points) but more importantly, to enable you to provide the effective counselling to your ED patients as part of your professional role as a healthcare provider. The course structure consists fo four chapters followed by an assessment: Chapter 01: Epidemiology & Aetiology of Erectile Dysfunction Chapter 02: Anatomy & Pathophysiology of the Penis Chapter 03: Management & Treatment Options for Erectile Dysfunction Chapter 04: Role of Pharmacists in Erectile Dysfunction Assessment: (20 randomized quiz questions, passing mark 80%, unlimited attempts) Feedback Lastly, we invite you to provide feedback regarding this course so that can it can be continuously improved and made relevant, practical and useful for you and others.